PENGARUH RELATIONSHIP BENEFITS PADA RELATIONSHIP CONTINUITY MELALUI RELATIONSHIP VALUE TERHADAP PELANGGAN PT. XYZ - Raymond Nathaniel Halim (Jurnal Strategi Pemasaran, 2016)
This study aimed to analyze the effect of Relationship Benefits to Relationship Continuity through Relationship Value towards the PT. XYZ's customers . This study will be conducted by distributing questionnaires to 30 respondents who have ever made a purchase from PT. XYZ more than 1 time. Analysis technique used is quantitative analysis technique.